Soil Tillage, Straw Mulching, and Microalgae Biofertilization in Potato Production in Conventional and Organic Systems - Yagi, Renato; Dobrychtop, Emanuelle C.; Bittencourt, Henrique v. H.; Andrade, Diva S.; Kawakami, Jackson; Soratto, Rogério P. [UNESP] (Springer Nature, 2024)
This study explores soil and fertilizer management techniques using winter cereal rye and Chlorella sorokiniana microalgae biofertilization alongside mineral and organic fertilizers for spring–summer potato cultivation in both conventional (CONV) and organic (ORG) production systems in subtropical environments. Traditional soil management, with a fallow period followed by subsoiling, plowing, and harrowing, served as the reference standard for comparisons with four alternative methods in CONV and ORG systems. In the CONV system, cereal rye plants were terminated with glyphosate and the alternative soil managements included (i) incorporating chopped cereal rye with standard soil tillage, (ii) no-till planting into chopped cereal rye, (iii) planting into chopped cereal rye after soil chiseling, and (iv) mulching chopped cereal rye residues on the ridges of potato planted after standard soil tillage. In the ORG system, the alternatives included (v) incorporating fresh cereal rye with standard soil tillage, (vi) no-till planting into standing fresh cereal rye plants, (vii) no-till planting into cereal rye terminated with a knife roller, and (viii) mulching whole cereal rye plants between the ridges of potato planted after standard soil tillage. Each soil management was combined with treatments of no fertilization or either mineral or organic fertilization with or without microalgae application. Amid severe water constraints, particularly due to La Niña events, standard soil tillage in CONV and no-tillage in ORG both on cereal rye crops respectively increased (39.5%) total tuber yield and number of tubers per plant (18.8%), showing themselves as potential conservation soil managements to potato crop. Microalgae with respective fertilizer application exclusively associated with chopped cereal rye residues on hills in CONV and with no-till planted into fresh plants of cereal rye in ORG favored tuber filling.
Keywords: Chlorella sorokiniana; Poultry litter; Secale cereale; Solanum tuberosum